1991
DOI: 10.1111/j.1708-8240.1991.tb00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Home Tooth Bleaching Gel Cytotoxic?

Abstract: Tooth whitening systems are widely used clinically and for home usage. The aim of this study was to determine the effects of two bleaching gels, each containing 10 percent and 15 percent carbamide peroxide, respectively, a ‘bleaching gel’ without carbamide peroxide, and carbamide peroxide alone on the viability of human endothelial cells in vitro in comparison with culture medium that acted as a negative control. The incubation period used was 30 minutes. A colorimetric viability assay (MTT assay) was employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 80 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…In the vital pulp, the pulpal fluid pressure is capable of reducing inward diffusion of chemicals [30]. In addition, there are sufficient mechanisms in the pulp that protect the tissue from free radicals generated from the reaction of hydrogen peroxide, so that the available levels of hydrogen peroxide would be significantly reduced [31]. Further studies must be conducted to determine the influence of the diffusion time on the amount of peroxide that actually reaches the pulp, as well as its relevance for cytotoxicity on pulpal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In the vital pulp, the pulpal fluid pressure is capable of reducing inward diffusion of chemicals [30]. In addition, there are sufficient mechanisms in the pulp that protect the tissue from free radicals generated from the reaction of hydrogen peroxide, so that the available levels of hydrogen peroxide would be significantly reduced [31]. Further studies must be conducted to determine the influence of the diffusion time on the amount of peroxide that actually reaches the pulp, as well as its relevance for cytotoxicity on pulpal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In vital pulp, the pulpal fluid pressure is capable of reducing inward diffusion of chemicals. [1920] Tse et al .,[21] reported that there are sufficient mechanisms in the pulp that protect tissue from radicals generated from the reaction of hydrogen peroxide reaching into the pulp and defense mechanism of pulp would significantly reduce the available level of hydrogen peroxide. Therefore, the amount of hydrogen peroxide reaching the vital pulp may be less than in in vitro conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it has been shown that both hydrogen peroxide[1718] and CP penetrate enamel and dentin and also enter the pulp chamber[19–21] and pulpal enzymes are significantly inhibited by hydrogen peroxide. [22]…”
Section: Introductionmentioning
confidence: 99%
“…For example, Peterkofsky and Prather (1977) reported an ID50 of approximately 0.008 mmol/L H1202 for chick embryo fibroblasts, but this was for 24 h of incubation with H1202. Tse et al (1991) applied either a 2 mg/mL Rembrandt Lighten with 10% CP or 3 mg/mL of the same agent with 15% CP (21 and 32 mmol/L H1202, respectively) directly to cultured human umbilical-cordvein endothelial cells and found that both H1202 concentrations reduced MTT activity to approximately onequarter (ID75) of negative control level in 30 min. In the present experiments, a one-hour incubation of H1202…”
Section: Discussionmentioning
confidence: 99%